An outlook on the customers and advertisers acceptance on the neighbourhood director / Andi Suswandi Shamsuddin - Shamsuddin, Andi Suswandi (1997)
Telekom Publications Sdn. Bhd. is known as the sole publisher of the accurate and complete directory information called Yellow Pages. The main purpose of it is to provide an information that is vital towards the stimulation of commercial. With the stable growth in the economy sector and an encouraging development of technology, political and education, the need for fast and accurate information among publics is also increasing. Although Malaysia is moving towards the cyber globalization with the MultiMediaSupercorridor but the printed material or directory books are still needed and probably saves time. With more specific segmentation, TPSB plans to produce a new directory that is known as the Neighbourhood Directory. This directory will covers only four specific area in the Klang Valley, that is Bangsar, Taman Tun Dr. Ismail, Damansara (Damansara Utama, Damansara Height, Damansara Jaya) and Bandar Utama. This directory is basically the same concept as the Yellow Pages.